Development of measures to improve milk quality and safety during production - Shkromada, Oksana; Skliar, Oleksandr; Paliy, Andriy; Ulko, Larysa; Gerun, Inessa; Naumenko, Oleksandr; Ishchenko, Katerina; Kysterna, Olesia; Musiienko, Oleksii; Paliy, Anatoliy (Eastern-European Journal of Enterprise Technologies, 2019)
The number of somatic cells in cow milk affects its quality indicators, grade and safety. The level of somatic cells in milk depends on the state of the udder in animals. That is why it is important to diagnose sub-clinical mastitis of cows and prevent its occurrence. The performed studies made it possible to determine the histological spectrum of somatic cells in cows of the Ukrainian black-speckled dairy breed. It was experimentally proved that the microorganisms, selected from the cow udder skin are identical to the microflora, which causes sub-clinical mastitis disease in cows. As a result of the conducted research, the way of passing pathogens of mastitis infection through the rubber of milk glasses of milking equipment was identified. In addition, the spectrum of the pathogens of sub-clinical mastitis was determined and the scheme for disease prevention and its spreading among the herd of dairy cows was developed. The experimental researches proved the efficiency of using rapid mastitis test that makes it possible to remove from herds the cows with poor quality milk in due time. The emergence of ketone bodies in milk increases its acidity and reduces the milk quality. Acidity index characterizes the nutritional value of milk and is controlled when milk is accepted to a dairy factory. In this case, an enterprise loses money due to milk grade lowering. The method for prevention and treatment of ketosis in cows based on chelates of metals due to the improvement of metabolic processes in cows’ rumen was experimentally developed. The performed studies revealed the interrelation between the state of the rumen microflora and emergence of acetonemia in cows. Thus, the suggested measures provide an opportunity to enhance the quality and safety of cow milk by reducing the number of animals with symptoms of mastitis and ketosis in a herd.